Black butler IV - Toboso, Yana, 1984- (Black butler, 2011)
Earl Phantomhive and his butler, Sebastian, are called to action by Queen Victoria after a number of her citizens become the victims of some bizarre attacks, but the clues lead them straight to a Indian prince, who appears to have a remarkable butler of his own, and a new rivalry begins.